2009
DOI: 10.21608/fjard.2009.197061
|View full text |Cite
|
Sign up to set email alerts
|

FORAGING ACTIVITY OF THE SUBTERRANEAN TERMITE, Anacanthotermes ochraceus (Burmeister) (ISOPTERA : HODOTERMITIDAE) AT El-FAYOUM GOVERNORATE, EGYPT

Abstract: The foraging activity of the subterranean termite, Anacanthotermes ochraceus (Burmeister) (Isoptera: Hodotermitidae) was studied at El-Saidia village, Sennoures district, El-Fayoum Governorate, Egypt, throughout the two successive years 1997 and 1998 using perforated Polyvinyl chloride (P.V.C.) traps filled with corrugated cardboard paper then buried into the soil to a depth of 30 cm. Traps were replaced with new ones at monthly intervals. Parameters used for assessing foraging activity are % visited traps, nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The pH of canned tuna increased significantly after 9 months of storage ( p < .05). The higher pH values in canned samples may be due to the formation and accumulation of some amino acids and volatile nitrogen compounds such as NH 3 as a result of the breakdown and proteolysis of proteins during heat treatment (El‐Sherif, 2001). Czerner et al (2015) studied the effect of canning process on the physicochemical properties of Engraulis anchoita and found that the pH of the fresh fish was 6.07 which after canning and during storage at room temperature due to the breakdown of protein into basic products such as ammonia, amines, and hydrogen sulfide which increased to 6.12.…”
Section: Resultsmentioning
confidence: 99%
“…The pH of canned tuna increased significantly after 9 months of storage ( p < .05). The higher pH values in canned samples may be due to the formation and accumulation of some amino acids and volatile nitrogen compounds such as NH 3 as a result of the breakdown and proteolysis of proteins during heat treatment (El‐Sherif, 2001). Czerner et al (2015) studied the effect of canning process on the physicochemical properties of Engraulis anchoita and found that the pH of the fresh fish was 6.07 which after canning and during storage at room temperature due to the breakdown of protein into basic products such as ammonia, amines, and hydrogen sulfide which increased to 6.12.…”
Section: Resultsmentioning
confidence: 99%
“…Food consumption is more or less moderate during both summer and autumn; it recorded two distinct peaks; one in the 1 st half of May and the other in the second half of October. Several authors assessed the surface foraging activity of different species of subterranean termites depending on the food consumption (Brain, 1978;Ali et al, 1982;El-Sebay, 1993;El-Sherif et al, 2009;Abd El-Latif, 2013 andSolaiman, 2014).…”
Section: Food Consumptionmentioning
confidence: 99%
“…Both food consumption and soil translation rates are the most precise and more quantitatively accurate parameters for the assessment of termite foraging activity. (El-Sherif, et al 2009).…”
Section: Food Consumptionmentioning
confidence: 99%
See 1 more Smart Citation